The effects of an individualised ICT-based music education programme on primary school students' musical competence and grades. (2nd April 2016) - Hernández-Bravo, Juan R.; Cardona-Moltó, M. Cristina; Hernández-Bravo, José A.
Abstract : The purpose of this study was to examine the effect of an information and communications technology (ICT)-based individualised music education programme on primary students' musical competence. A 2 × 3 aptitude treatment interaction factorial design was used to assess the impact of the programme as a function of students' musical aptitude (MA) (low–average–high) and type of intervention (experimental vs. control). Participants were a convenient sample of 90 fifth- and sixth-grade students drawn from one public primary school in Albacete, Spain. Results indicated that average and high musically able participants developed a significantly higher competence in audition, vocal expression, instrumental expression, musical language, movement and dance, as well as in arts and culture in the ICT-based than in the non-ICT-based programme, while those with low MA appeared to benefit more from the non-ICT-based programme suggesting that students responded differently to the two types of interventions. Results are discussed in terms of implications to better adapt music teaching for student diversity.